Professional development of educators aimed at research and change of their own educational practice - Slunjski, Edita (Array, 2008)
Traditional forms of professional development of education experts are based on the assumption that a path from information to knowledge and from knowledge to practice is linear, simple and that both (knowledge and practice) can be obtained mechanically. However, professional development should result not only in the improvement of knowledge but even more in the changes of belief and behaviour of educators, and the lecture (informative) type of professional development cannot by itself lead to this. Quality of living, learning and education of students in an educational institution is not determined by individual pedagogical or methodical interventions of educators but by the entire context of the educational institution, of which a educator is an integral part and which he or she can change according to his or her degree of its understanding. For educators it is necessary to raise the level of understanding of the context of their own educational institution and to shape new believes on which new skills and capabilities are based, which are needed for development of a more quality educational practice. For this reason professional development of educators should be made in the educational institution itself, and should be aimed at evolution of their research and reflexive skills. By joint research, educators are qualified for better understanding and graduate change and development of their own practice and in this way they become "reflexive practitioners" i.e. "class ethnographers". Culture of common research, decision making and coordinated action should be developed in an educational institution, in which each individual is co-responsible for creation of the organization which is capable for individual and group research and continuous self-development, leading to continuous development of educational practice.